Development of Socio-Scientific Inquiry-Based Learning Worksheets on Coordination System Material to Improve Senior High School Students’ Critical Thinking Skills - Silvia, Cindy; Jayanti, Ummi Nur Afinni Dwi (Jurnal Paedagogy, 2026)
This study aims to develop and validate socio-scientific inquiry-based learning worksheets for the coordination system topic and to examine their effectiveness in enhancing senior high school students’ critical thinking skills. The study involved 25 eleventh-grade students from SMA Swasta Harapan Paya Bakung and employed a Research and Development (R&D) approach based on the 4D model, combined with a One-Group Pretest–Posttest design. The quality of the developed worksheets was assessed through expert validation, while their practicality was evaluated based on teacher and student responses. The effectiveness of the worksheets was measured using critical thinking assessments developed according to Facione’s indicators and analyzed using N-Gain scores. The results showed that the developed worksheets achieved a high level of validity, with validation scores exceeding 85%, and received positive responses from both teachers (94%) and students (90.6%). Furthermore, students demonstrated significant improvement in critical thinking skills, as indicated by an average posttest score of 90.72 and an N-Gain value of 0.85, which was categorized as high. These findings indicate that socio-scientific inquiry-based learning (SSIBL) worksheets serve as an effective learning resource for fostering critical thinking skills while promoting active, contextual, and meaningful biology learning experiences.